Oscillations of Second Order Impulsive Differential Equations with Advanced Arguments (Global Journal of Science Frontier Research, 2018)
A comparison theorem providing sufficient conditions for the oscillation of all solutions of a class of second order linear impulsive differential equations with advanced argument is formulated. A relation between the oscillation (non-oscillation) of second order impulsive differential equations with advanced arguments and the oscillation (non-oscillation) of the corresponding impulsive ordinary differential equations is established by means of the Lebesgue dominated convergence theorem. Obtained comparison principle essentially simplifies the examination of the studied equations.
Keywords: impulsive differential equations; comparison theorem; advanced arguments; second order; oscillation